2018
DOI: 10.1089/cap.2017.0047
|View full text |Cite
|
Sign up to set email alerts
|

A 6-Month Open-Label Extension Study of Vortioxetine in Pediatric Patients with Depressive or Anxiety Disorders

Abstract: Objectives: In this 6-month open-label extension (OLE) of NCT01491035 (a 14-day, open-label, pharmacokinetic/safety lead-in study), the long-term safety and tolerability of vortioxetine (5–20 mg/day) were investigated in children and adolescents with a DSM-IV-TR™ diagnosis of depressive or anxiety disorder in the United States or Germany. The study also was designed to provide data to inform dose selection and titration in future pediatric studies with vortioxetine.Methods: Safety evaluations included spontane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…16 This study confirmed that vortioxetine steady-state exposure with both doses was comparable to that observed in adult populations. 16,32 This study supported the acceptable safety profile of vortioxetine previously seen in an adolescent MDD population, 16,25 with nausea as the most common AE, as seen in adult patient populations. 11 Variability in the incidence of specific AEs compared with adult populations, most specifically, suicide-related events, might be expected based on the elevated risk of suicide-related behavior versus placebo observed in pediatric MDD trials.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…16 This study confirmed that vortioxetine steady-state exposure with both doses was comparable to that observed in adult populations. 16,32 This study supported the acceptable safety profile of vortioxetine previously seen in an adolescent MDD population, 16,25 with nausea as the most common AE, as seen in adult patient populations. 11 Variability in the incidence of specific AEs compared with adult populations, most specifically, suicide-related events, might be expected based on the elevated risk of suicide-related behavior versus placebo observed in pediatric MDD trials.…”
Section: Discussionsupporting
confidence: 77%
“…The selected doses of vortioxetine 10 and 20 mg/day in the double-blind treatment period were based on an open-label pediatric PK study showing PK (as assessed by Cmax and AUC0- 24) and safety/tolerability profiles of vortioxetine comparable to those seen in adults; hence, supporting the dose range of 5 to 20 mg/day. 16,25 Patients randomized to vortioxetine 10 mg received 5 mg/day for 2 days, and those randomized to vortioxetine 20 mg received 5 mg/day for 2 days followed by 10 mg/day and 15 mg/day for the next 2 days each before receiving the end dose. Patients in the fluoxetine arm received 10 mg/day for 6 days before the end dose of 20 mg/day.…”
Section: Treatmentsmentioning
confidence: 99%
“…In addition, patients were asked to return all unused study medication. Patients who completed the main study period, if judged advisable by the investigator, were offered to continue in an optional, 6-month, open-label, flexible-dose extension trial (Findling et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Consistently, a randomized, double-blind, placebo-controlled, proof-of-concept study performed in a group of ADHD patients aged 18-55 years old showed an overall reduction in the interference of ADHD symptoms with psychosocial functioning, alongside a reduced rate of adverse effects [10]. Although off-label, the efficacy and tolerability of VTX in children and adolescents with a depressive or anxiety disorder have been confirmed through a prospective open-label multinational multisite multidose trial, and its benefits as an addon therapy to MPH have already been investigated in a 15-year-old ADHD girl [11,12]. Interestingly, another antidepressant, the selective norepinephrine reuptake inhibitor (NRI) viloxazine, has been recently approved in the USA for the treatment of ADHD in pediatric patients aged 6-17 years [13].…”
Section: Discussionmentioning
confidence: 99%